Analisis Potensi Daerah Rawan Longsor di Kecamatan Bawen dan Tuntang dengan Metode Simple Additive Weighting (SAW) - Mira; Merryana Lestari; Candra Gudiato; Sri Yulianto Prasetyo; Charitas Fibriani (Institut Shanti Bhuana, 2021)
The high intensity of rainfall at the end of 2020 and early 2021 not only caused several areas in Indonesia to be flooded but also landslides. Landslides can occur due to soil movements in the rainy season and are influenced by tectonic conditions in Indonesia which are always changing. Bawen and Tuntang Districts are two districts in Semarang Regency, Central Java. Both areas were hit by floods and landslides in April 2020. The material and moral losses of the local population are inevitable. To take precautions as early as possible in order to reduce future losses, it is necessary to conduct research on the potential of landslide-prone areas in Bawen and Tuntang Districts. The analysis was carried out using the Simple Additive Weighting (SAW) method to calculate the percentage of an area where landslides occurred. The parameters used include land cover, slope, rainfall, Soil Adjusted Vegetation Index (SAVI), Normalized Difference Vegetation Index (NDVI), and Normalized Difference Wetness Index (NDWI). The results of this study indicate that the level of landslide vulnerability in Bawen and Tuntang Districts is classified as